Development of Thermodynamics Law Electronic Book Using 3D Pageflip, Macromedia Flash, and Ispring Quizmaker Applications for Physics Education Students (Jurnal Pendidikan Fisika, 2023)
This research aimed to describe the development process and to figure out the validity level, practicality level, and effectiveness of the thermodynamics law electronic book using 3D Pageflip, Macromedia Flash, and Ispring Quizmaker applications for Physics Education students at Alauddin Makassar State Islamic University. This study fell under the category of research and development (R&D). The research design followed the 4D development model: Define, Design, Develop, and Disseminate. A small-scale trial was conducted to 35 physics education students of the sixth semester in the academic year of 2022/2023. Research instruments included validation sheets, electronic book feasibility observation sheets, and questionnaires assessing responses from professors and students regarding the electronic book. The data were analyzed using descriptive statistics. The results of data analysis reveal that the electronic book's validity level obtained an Aiken's V index value of 0.68, categorized as highly valid, indicating suitability for use. Furthermore, the data from student observation sheets showed that 94% of students are in favor of the book, while professors' response was 100% positive, and students' response was 49% very positive and 40% positive, indicating that the electronic book was considered practical. Finally, the effectiveness level of the e-book through learning outcome test analysis achieved an 83% completion rate, indicating that the electronic book developed is effective to use.